ANALYSIS OF LEGAL PROTECTION AGAINST CHILD EXPLOITATION : CASE STUDY OF BEGGARS IN SIDOARJO CITY - Tresnia Octaviani Sumarsono; Emy Rosnawati (PT. Antis International Publisher, 2025)
Objective: This research is a type of normative research with a statutory and regulatory approach. Method: Primary legal materials used include Law No.35/2014 concerning Child Protection, Sidoarjo Regional Regulation No. 2/2023 concerning the Implementation of a Child Friendly Regency, Sidoarjo Regent Regulation No. 7/2022 concerning Position, Organizational Structure, Duties and Functions and Work Procedures of the Social Service, Sidoarjo Regency. Secondary legal materials used include books, journals and other literature relevant to the cases studied. Analysis of legal materials is carried out using deductive analysis methods. Results: The research results show that legal protection against exploitation of minors in Sidoarjo Regency has been implemented in accordance with applicable regulations and ensures compliance with standards set to protect children's rights from exploitation. However, there are still challenges in terms of coordination, limited resources and public awareness that need to be overcome to ensure more effective child protection. Novelty: This research highlights the implementation of legal protection against the exploitation of minors in Sidoarjo Regency through the analysis of regional regulations and statutory provisions, emphasizing the alignment between local and national frameworks to strengthen child protection efforts.